Contribuições da História da Ciência para o ensino de Química: o modelo científico da geometria molecular e o currículo - Parisi,Sophia Rodrigues (2021)
This work promotes the discussion of the use of models in the classroom and brings to debate the need to explain the limits and transformations present in these representations. For this, it is pointed out the use of the History of Science as a helping tool in the learning process, taking into account that its bases represent great relevance to the teaching process and it can bring the necessary contextualization for the understanding of the construction of scientific knowledge for the student. The model we chose to guide our research was the molecular geometry, due to the threedimensionality of the molecules, which makes a greater power of imagination of the students in the mental conception of these models and in the sense of the spatial idea of the arrangement of atoms in molecules necessary. This study develops aiming to verify how the models are dealt with in Chemistry textbooks, how their description is made, and the type of historical approach is used in the conception of the content. Parallel to that, it is also considered, from the study of original texts perspective, how the construction and development of molecular geometry models occurred. It is also analyzed studies that describe how it was included in textbooks. The discussion of the interface between the History of Science and the Chemistry teaching, in this work, can contribute to reflection and discussion of the genesis and transformation of concepts and in the analysis of the various models of knowledge elaboration. In addition, the analysis of the selected textbooks made it possible to verify that the historical approach of the contents goes into another direction taking into account the objectives listed in the National Curricular Parameters and in the National Guide of Chemistry textbook 2018, since they do not meet their objectives completely.